Triterpene glycosides of Lupinus angustifolius - Woldemichael, Girma Moges; Wink, Michael (Phytochemistry reviews, 2002)
Investigation of whole seeds of Lupinus angustifolius L. (Leguminosae) yielded the two triterpenoid saponins with branched monosaccharide chain 3β,21β,22β,24-tetrahydroxyolean-12-en-3-O-α-l-rhamnopyranosyl-(1→3)-[α-l-rhamnopyranosyl-(1→2)]-β-d-galactopyranosyl-(1→2)-β-d-glucuronopyranoside (3) and 3β,21β,22β,24-tetrahydroxyolean-12-en-3-O-α-l-rhamnopyranosyl-(1→3)-[α-l-rhamnopyranosyl-(1→2)]-β-d-galactopyranosyl-(1→2)-β-d-glucuronopyranosyl-21-O-α-l-rhamnopyranoside (4) along with the known compounds soyasaponin I (1) and 3β,21β,22β,24-tetrahydroxyolean-12-en-3-O-α-l-rhamnopyranosyl-(1→2)-β-d-galactopyranosyl-(1→2)-β-d-glucuronopyranosyl-21-O-α-l-rhamnopyranoside (2). The structures of the compounds were elucidated using hydrolysis, FAB-MS and extensive NMR experiments. Compounds 2-4 showed moderate antifungal activity against Candida albicans with MIC values of 25, 25 and 30 μg/ml, respectively. Only soyasaponin I was found weakly hemolytic (HC50 >500 μg/ml).